Hacia una introducción selectiva al teatro en Portugal: breve encuadramiento - Coelho, Rui Pina (2018)
This text is divided in two parts. Firstly, I deal with the evolution on Portuguese theatre from the post-second world war period until present day. I’m focusing on the experimentalism of the forties, characterized by an urge for renewal and modernization; the constitution of a highly politicized independent theatre movement, in the seventies; and the plurality of contemporary Portuguese theatre. Secondly, I deal with the alleged inability of Portuguese writers for playwriting, signalling the most significant names of the post Carnation Revolution, on the 25th of April 1974, to present days.